Electric control of Dirac quasiparticles by spin-orbit torque in an antiferromagnet - Šmejkal, L.; Železný, J.; Sinova, J.; Jungwirth, T. (American Physical Society, 2017)
Spin orbitronics and Dirac quasiparticles are two fields of condensed matter physics initiated independently about a decade ago. Here we predict that Dirac quasiparticles can be controlled by the spin-orbit torque reorientation of the Néel vector in an antiferromagnet. Using CuMnAs as an example, we formulate symmetry criteria allowing for the coexistence of topological Dirac quasiparticles and Néel spin-orbit torques. We identify the nonsymmorphic crystal symmetry protection of Dirac band crossings whose on and off switching is mediated by the Néel vector reorientation. We predict that this concept verified by minimal model and density functional calculations in the CuMnAs semimetal antiferromagnet can lead to a topological metal-insulator transition driven by the Néel vector and to the topological anisotropic magnetoresistance.